General characteristics of patches and their applications in the pharmaceutical industry (Research, Society and Development, 2023)
Transdermal patches are multilaminated, flexible, medicated structures that have bioadhesive properties, they are essentially made up of a medication delivery system and an adhesive layer for fixation to the skin, providing constant and prolonged absorption. They are examples of systemic topical formulations that, due to their innovations at promising levels, are being increasingly studied in the pharmaceutical industry community with the aim of obtaining innovation and new technologies. These innovations are based on the alteration of transdermal delivery systems, enabling the permeation of drugs with a variety of physicochemical properties. In view of the growing interest, even though there is a small group of medicines being marketed in Brazil, the main objective of this study was to carry out a literature review, for greater clarification and considering the structure and general constitution of patches, the promising release innovations, current quality control, applications and the advantages and disadvantages. It was identified that transdermal patches offer notable advantages to patients in terms of the expected therapeutic results, mainly due to the liver dispensing in filtering the drug in the hepatic first pass effect.